The effect of lighting conditions and use of headlights on drivers’ perception and appraisal of approaching vehicles at junctions - Lee, Yee Mun; Sheppard, Elizabeth (Taylor & Francis, 2018)
Use of Daytime Running Lights (DRL) is mandatory in many countries for motorcycles, and in some for cars. However, in developing countries DRLs may be optional or compliance low. The effect of car or motorcycle headlights and lighting conditions on Malaysian drivers’ ability to perceive and judge the safety of pulling out was investigated. Stimuli were photographs depicting either daytime or nighttime taken at a T-junction with approaching vehicles with headlights on or off. Headlights improved drivers’ ability to perceive cars and motorcycles in the nighttime photographs but not the daytime photographs, although this could be due to the bright weather in the photographs. Drivers judged it less safe to pull out when approaching motorcycles had headlights on than off, regardless of the lighting conditions, supporting the utility of DRL for motorcycles. Headlights did not affect judgments for cars, questionning the utility of DRL for cars.